Online Contract And The Concept Of Caveat Emptor A Compapdtive Study Between Islamic Perspective And Malaysian Contract Law. - Syahi'h Abdul Shukor; Sheikh Salim Sheikh Salleh; Adibah Abdul Ghafar; Dina Imam Supaat; Farah Salwani Muda @ Ismail (Universiti Sains Islam Malaysia, 2024)
The evolution of the Internet has lead to many discoveries and lessens the hassle in our daily life. Computer networks are playing an increasingly vital role day by day. Internet is not only used as a tool to gather information, but also as a way of conimunication and interaction. Internet has been regarded as tlie easiest, simplest and paperless mcthod in making businesses instantly. These businesses, which appear through the net, are known as e-commerce or e-business. These online transactions are actually able to attract millions of people worldwide. However, online contracts that are done totally through the net without any physical contact between tlie scllcr and buyer may cxposc consumcrs to fraud and insecurities. Therefore, it is submitted that thcrc should bc ccrtain mechanisms to control this practice, and to ensure that tlic consumer's rights are well protected by the laws and the authorities. Until now, the Malaysian government has passed several statutes, relating to Cyber Laws to ensure tlic success of the Multinicdia Super Corridor projects. The study aims to discover the lcvcl of Icgal awarcncss among thc Intcrnet users pertaining to online contracts particularly on onlinc sho1?1>ingT. he scope of this study is limited to Internet ilscrs in Klang Vallcy and Sclangor only. Bascd on the survey rcsult, the researchers will try to invcstigatc tlic trend, practicc and the bcncfits of online shopping among thcsc consumcrs. Bcsidcs that, the study will cxplol-c the principle of cuveut erlzptor i.e. "let the buyers bcwarc" in online contr:lcts and also to analyze this principle under the Islamic perspective. It is hoped that the findings, suggestions and analysis of this research woiild further enliance tlic dcvclopnicnt of online contracts in Malaysia.